Development of a Pilot Data Management Infrastructure for Biomedical Researchers at University of Manchester – Approach, Findings, Challenges and Outlook of the MaDAM Project - Meik Poschen; June Finch; Rob Procter; Mhorag Goff; Mary McDerby; Simon Collins; Jon Besson; Lorraine Beard; Tom Grahame (International Journal of Digital Curation, 2012)
Management and curation of digital data has been becoming ever more important in a higher education and research environment characterised by large and complex data, demand for more interdisciplinary and collaborative work, extended funder requirements and use of e-infrastructures to facilitate new research methods and paradigms. This paper presents the approach, technical infrastructure, findings, challenges and outlook (including future development within the successor project, MiSS) of the ‘MaDAM: Pilot data management infrastructure for biomedical researchers at University of Manchester’ project funded under the infrastructure strand of the JISC Managing Research Data (JISCMRD) programme. MaDAM developed a pilot research data management solution at the University of Manchester based on biomedical researchers’ requirements, which includes technical and governance components with the flexibility to meet future needs across multiple research groups and disciplines.